Early breakdown of the blood-retinal barrier in diabetes. - Cunha-Vaz, J. (1975)
The blood-retinal barrier plays an important part in the processes of retinal pathophysiology. A new clinical method for the study of the blood-retinal barrier by vitreous fluorophotometry appears to satisfy the necessary requirements in that it is quantitative and shows good reproducibility and high sensitivity. The application of this method to a series of diabetic patients with apparently "normal" fundi revealed the presence of a significant breakdown of the blood-retinal barrier in the early stages of retinal involvement in diabetes. The extent of the breakdown can be measured allowing for comparative and evolutionary evaluations. The disturbance of the blood-retinal barrier, as evidence by vitreous fluorophotometry, appears before microaneurysms or capillary closure can be demonstrated by fluorescein angiography.